2020
DOI: 10.1038/s41598-020-70000-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct and quantitative analysis of altered metabolic flux distributions and cellular ATP production pathway in fumarate hydratase-diminished cells

Abstract: Fumarate hydratase (FH) is an enzyme in the tricarboxylic acid (TCA) cycle, biallelic loss-of-function mutations of which are associated with hereditary leiomyomatosis and renal cell cancer. However, how FH defect modulates intracellular metabolic fluxes in human cells has remained unclear. This study aimed to reveal metabolic flux alterations induced by reduced FH activity. We applied 13 c metabolic flux analysis (13 C-MFA) to an established cell line with diminished FH activity (FH dim) and parental HEK293 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This analysis revealed that NADPH consumption and NADH production were reduced in FH-diminished cells, suggesting that the altered redox balance may have caused decreased proline synthesis from glutamine. This analysis also demonstrated that FH-deficiency shifts ATP production towards glycolysis, allowing for increased resistance to mitochondrial inhibitors [126]. Together, these studies exemplify how iMFA can parse key drivers of cancer reprogramming from the multitude of metabolic alterations that occur.…”
Section: Compensating For Genetic Loss Of Functionmentioning
confidence: 60%
“…This analysis revealed that NADPH consumption and NADH production were reduced in FH-diminished cells, suggesting that the altered redox balance may have caused decreased proline synthesis from glutamine. This analysis also demonstrated that FH-deficiency shifts ATP production towards glycolysis, allowing for increased resistance to mitochondrial inhibitors [126]. Together, these studies exemplify how iMFA can parse key drivers of cancer reprogramming from the multitude of metabolic alterations that occur.…”
Section: Compensating For Genetic Loss Of Functionmentioning
confidence: 60%
“…It is reported that decreases of FH can lead to adenosine triphosphate depletion by crippling tricarboxylic acid cycle and oxidative phosphorylation. 25 Therefore, we speculate that because of the involvement of higher frequency and titer of FH, ACLF patients with good prognosis have an advantage in hepatocyte regeneration compared with ACLF patients with poor prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…For example, depletion of fumarate hydratase (FH) was identified as a top hit in the screen, activating the ARE-GFP reporter, consistent with studies showing fumarate hydratase deficiency increases cellular levels of the KEAP1-reactive metabolite fumarate. 10,11,16 Further, depletion of transketolase (TKT) or transaldolase (TALDO1), two enzymes in the nonoxidative branch of the PPP, also resulted in ARE-GFP reporter activation. This result likely reflects the ability for these enzymes to reversibly catalyze reactions with the glycolytic metabolite Ga3P, which we have previously shown to activate NRF2 through direct modification of KEAP1.…”
Section: Resultsmentioning
confidence: 99%